Interferon is associated with improved survival for node-positive cutaneous melanoma: a single-institution experience. (9th April 2018) - Oliver, Daniel E; Sondak, Vernon K; Strom, Tobin; Zager, Jonathan S; Naghavi, Arash O; Sarnaik, Amod; Messina, Jane L; Caudell, Jimmy J; Trotti, Andy M; Torres-Roca, Javier F; Khushalani, Nikhil I; Harrison, Louis B
Aim: We assessed the role of adjuvant interferon on relapse-free survival (RFS), distant metastasis-free survival (DMFS) and overall survival (OS) in node-positive melanoma patients.Methods: We retrospectively reviewed 385 node-positive patients without distant metastatic disease treated from 1998 to 2015. The surgery was therapeutic lymph node dissection (LND, n = 86) or sentinel lymph node biopsy ± completion LND (n = 270). 128 patients (33.2%) received adjuvant interferon.Results: After a median follow-up of 70 months, interferon was associated with improved RFS (hazard ratio [HR]: 0.55; p < 0.001), DMFS (HR: 0.59; p < 0.001) and OS (HR: 0.61; p = 0.003), controlling for tumor and nodal stage, node size, sex, primary site, adjuvant therapy and extracapsular extension. In an exploratory age-matched comparison of patients treated with (n = 67) and without (n = 233) adjuvant immunotherapy, interferon still showed improved RFS, DMFS and OS.Conclusion: Adjuvant interferon appears to improve OS among node-positive melanoma patients in a modern experience, providing context for comparison in the adjuvant therapy landscape.